Anningasaura, a basal plesiosaurian (Reptilia, Plesiosauria) from the Lower Jurassic of Lyme Regis, United Kingdom - Vincent, P; Benson, R (2012)
The plesiosaur specimen NHMUK OR49202, from the Lias Group of Lyme Regis, consists of a complete skull, palate, and mandible, with eight associated cervical vertebrae, including the atlas-axis complex. This juvenile plesiosaur specimen was originally referred to Plesiosaurus macrocephalus. However, reexamination indicates that it does not belong to Plesiosaurus and comparison with the type specimen of Plesiosaurus macrocephalus (NHMUK OR1336) suggests that it is taxonomically distinct. Therefore, NHMUK OR49202 is made the holotype of a new genus and species: Anningasaura lymense. The specimen possesses plesiomorphic characters, including premaxillae that do not separate the frontals on the midline, narrow cranioquadrate passages, lack of a constricting groove around the occipital condyle, and several autapomorphies not observed in other plesiosaurian taxa: posteromedial processes of the premaxillae (or possible anterior portion of the frontal) forming a dorsoventrally thick, mediolaterally expanded platform; supplementary foramen penetrating the parietal sagittal crest; absence of a pterygoid-vomerine contact; absence of a contact between the pterygoids in palatal aspect; cultriform process of the parasphenoid wider mediolaterally than the combined posterior interpterygoid vacuities; and two closely spaced foramina in the lateral surface of the exoccipital. Anningasaura lymense is a plesiomorphic Early Jurassic taxon, and provides anatomical data that clarify the early evolutionary history of Plesiosauria. © 2012 Taylor and Francis Group, LLC.